Performance of hybrid aluminium–composite columnar tube under axial crush force - Paruka, Perowansa; Maleque, Md. Abdul; Md Shah, Md Kamal (2014)
This work presents an experimental investigation on the influence of number of layers in the overwrap hybrid composite columnars under repeated axial crushing force. Three columnar specimens are fabricated by hand lay-up process, made of combination of an aluminium thin square hollow structure with external protection using an isophathalic polyester resin reinforced with orientation angle of 0/90° glass fiber skin. In determining the energy absorption capacity, the crushed hybrid composite tubes are made using one-layer, two-layers and three-layers to determine the use of such fibers in structural automotive applications. Quasi-static crush test for these tubes was done using INSTRON machine with axial loading. The results showed that crush force and number of layers are related with the enhancement of energy absorption before structures collapse. It is found that the energy absorption properties of the crushed hybrid composite columnars have increased significantly by adding the number of layers in the overwrap.